A cross-national comparison of the Twitter feeds of popular alcohol brands in India and Australia. (4th March 2019) - Gupta, Himanshu; Lam, Tina; Pettigrew, Simone; Tait, Robert J.
Abstract: Aims: To evaluate (i) the types of techniques alcohol marketers utilise to facilitate user engagement with content on leading Indian and Australian Twitter alcohol brand pages and (ii) the extent to which users engage with this content in two diverse national contexts. Methods: The 10 alcohol brands per country with the greatest Twitter presence were identified based on the number of 'followers'. Number of tweets, photos, and videos were collected and the type of content noted for each brand between 1 January 2016 and 29 February 2016. The data were analysed via an inductive coding approach using NVivo10. Results: In total, the brands had accumulated up to 150, 386 followers (Indian: 110, 032; Australian: 40, 354). The techniques utilised were a mix of those that differed by country (e.g. India: sexually suggestive content versus Australia: posts related to the brand's tradition or heritage) and generic approaches (e.g. alcohol sponsorship of sport, music, and fashion; offering consumption suggestions; organising competitions; giveaways; and use of memes). Conclusions: The flexibility of Twitter, which complements traditional marketing, allows brands to adapt and deliver their online alcohol content in specific national contexts and to capitalise on the cultural meanings users invoke in their interactions with the brands.